Proposal of a Didactic Experiment to Understand the Limitations of Using Distributed Architectures for CAD - Beserra, David; Moreno, Edward David; Karman, Rubens; Galdino, Sergio (International Journal of Computer Architecture Education, 2015)
High-Performance Computing (HPC) is characterized by the intensive use of one or more types of computational resources. Typical HPC applications include processing large astronomical databases, simulating magnetic compounds, or bioprocessing applications. It is important that students, during their training in the use of Distributed Systems for HPC, understand how virtualization technologies and cloud tools can impact the performance of HPC activities. Based on this context, this work proposes a class with an experimental and comparative approach among various infrastructures, so that students, in addition to learning how to implement them in practice, can also understand their performance characteristics in HPC activities.